The usage of systemic enzyme therapy in combination treatment of erysipelas: the assessment by the pharmacoeconomic positions - N. Yu. Pshenichnaya; T. V. Moskovaya; A. V. Chistyakov; A. V. Usatkin (Журнал инфектологии)
Purpose. The aim of the study was to estimate the efficiency and economic feasibility of prescribing systemic enzyme therapy in the composition with standard etiotropic and pathogenetic therapy of erysipelas of lower extremities.Materials and methods. For this purpose, 62 patients with erysipelas of lower extremities were investigated. Standard therapy (antibiotics, non-steroids, anti-inflammatories) was administered in the 1th group of patients (n=32), patients of the 2th group (n=30) received natural systemic proteolytic enzymes within the acute period of disease additionally to the basic scheme of therapy. The clinic-economic parameters such as cost of illness and the indicator “cost-efficiency” were estimated.Results. The study has revealed the clinic and economic efficiency of systemic enzyme therapy in the combination therapy of erysipelas, which was confirmed by significant reduction of duration of in-patient treatment and decreasing the rate of recurrence of the disease, reduction of the full cost of the disease and the level of cost-effectivenes.Conclusion. Use of systemic enzymes is economically feasible and can reduce the full cost of treatment andincrease its efficiency